2014
DOI: 10.3892/etm.2014.2016
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiothoracic ratio, left ventricular size and systolic function in patients undergoing computed tomography coronary angiography

Abstract: The present study aimed to investigate the association between cardiothoracic ratio (CTR) and left ventricular (LV) systolic function parameters in patients with or without preserved LV ejection fraction (LVEF). A total of 203 subjects suspected with coronary artery disease underwent chest radiography and dual source computed tomography coronary angiography (DSCT-CA). The LV systolic function parameters: LV end-diastolic volume index (LVEDVI), LV end-systolic volume index (LVESVI), and LVEF were measured from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…However, further progress was hampered by the fact that no statistical tool was available to compare the analytically derived nonlinear regression lines. Without any attempt for justification of a particular choice regarding the regression model, most studies persisted in using the linear approach for the full clinically relevant spectrum [7][8][9][10][11]. Three major shortcomings of the linear approximation refer to the fact that (i) the theoretical point where EF reaches 100% for small ESVi values is not respected; (ii) the asymptotic range at lower EF values is not adequately incorporated; (iii) thus far the intrinsic nonlinearity of the intermediate range is insufficiently acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…However, further progress was hampered by the fact that no statistical tool was available to compare the analytically derived nonlinear regression lines. Without any attempt for justification of a particular choice regarding the regression model, most studies persisted in using the linear approach for the full clinically relevant spectrum [7][8][9][10][11]. Three major shortcomings of the linear approximation refer to the fact that (i) the theoretical point where EF reaches 100% for small ESVi values is not respected; (ii) the asymptotic range at lower EF values is not adequately incorporated; (iii) thus far the intrinsic nonlinearity of the intermediate range is insufficiently acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…20 The diagnostic accuracy from CT ratio for evaluation of function both LV and RV from many studies showed low accuracy. [21][22] In LV systolic function showed no significant association with CT ratio in patients with preserved left ventricular ejection fraction who had undergone computed tomography coronary angiography. But the CT ratio correlated with LV size and LV ejection fraction (LVEF) in patients with depressed LVEF.…”
Section: Original Article Smjmentioning
confidence: 88%
“…But the CT ratio correlated with LV size and LV ejection fraction (LVEF) in patients with depressed LVEF. 21 In another study, The CT ratio reflected atrial dilatation rather than ventricular dilatation. 22 Our study showed a significant positive correlation of CT ratio with symptomatic heart failure in pediatric heart disease.…”
Section: Original Article Smjmentioning
confidence: 92%
“…In the chronic heart failure population, it can be used for risk stratification with values >0.5 associated with poor prognosis 20 . Additionally, in patients with reduced ejection fraction (EF), CTR has shown some correlation with left ventricular volume index and systolic dysfunction 21 . In the pediatric population, an increased CTR is associated with increased total cardiac volume in the setting of valvular insufficiency 22 .…”
Section: Discussionmentioning
confidence: 99%